Born survivors : three young mothers and their extraordinary story of courage, defiance, and hope - Holden, Wendy, 1961- (New York, N.Y. : Harper, 2015)
Relates the true account of three pregnant women who met in Auschwitz, where they concealed their pregnancies from infamous Nazi doctor Josef Mengele and fought for their survival as well as the survival of their newborns as they embarked on a treacherous journey to freedom.
Keywords: Auschwitz (Concentration camp); Auschwitz (Poland: Concentration camp).; Holocaust, Jewish (1939-1945) -- Personal narratives; Jewish women in the Holocaust -- Biography; Holocaust survivors -- Biography; Holocaust, 1939-1945 -- Personal narratives; Jewish women -- Biography; Holocaust survivors -- Biography